Sosialisasi Peran Copywriting di Instagram Untuk Meningkatkan Penjualan Bisnis Pada Peserta Didik SMK El-Amin - Sri Winda Hardiyanti Damanik; Ririn Uke Saraswati; Sarmin Sarmin; Euis Ratnasari; Ananda Putri Rahmadhani; Nanda Nurkholillah; Nur Indah Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students at SMK EL-AMIN belong to the Generation Z, where many of them have already started their own businesses. However, some students running these businesses have not fully utilized social media, particularly Instagram, as a promotional tool. Therefore, a community service activity in the form of socialization was conducted for SMK EL-AMIN students in Cabangbungin sub-district, Bekasi regency, West Java. The aim of this socialization activity is to enhance the understanding and knowledge of SMK EL-AMIN students regarding the benefits of copywriting on Instagram in boosting business sales. The socialization activity was attended by 36 participants. The stages of the community service activity include preparation, implementation, and evaluation. After participating in the community service activity, the participants' awareness and knowledge of the benefits of copywriting in increasing business sales improved. Participants also gained insights into creative copywriting tips for business promotion. The socialization activity had a significant impact on increasing the awareness and knowledge of participants.